Analisis Tingkat Kemampuan Mahasiswa Akuntansi dalam Penyusunan Anggaran Komprehensif Perusahaan (Studi Kasus pada Mahasiswa Akuntansi Politeknik Negeri Padang) - Mustika, Rasyidah; Elvaretta, Dissa; Heriyanto, Randy; Susanti, Rini; Maulina, Vira (Universitas Batanghari Jambi, 2025)
This research aims to analyze the level of ability of accounting students in preparing a company's comprehensive budget. The research method used is a qualitative descriptive method with a case study design on Padang State Polytechnic accounting students. Primary data consists of observations of 28 accounting students. The research results found that the average ability of Padang State Polytechnic accounting students in preparing a company's comprehensive budget was still relatively high at 73.5%.